How do trainee doctors learn about research? Content analysis of Australian specialist colleges' intended research curricula. Issue 3 (15th March 2020) - Stehlik, Paulina; Noble, Christy; Brandenburg, Caitlin; Fawzy, Peter; Narouz, Isaac; Henry, David; Glasziou, Paul
Abstract : Objectives: Patients do better in research-intense environments. The importance of research is reflected in the accreditation requirements of Australian clinical specialist colleges. The nature of college-mandated research training has not been systematically explored. We examined the intended research curricula of Australian trainee doctors described by specialist colleges, their constructive alignment and the nature of scholarly project requirements. Design: We undertook content analysis of publicly available documents to characterise college research training curricula. Setting: We reviewed all publicly accessible information from the websites of Australian specialist colleges and their subspecialty divisions. We retrieved curricula, handbooks and assessment-related documents. Participants: Fifty-eight Australian specialist colleges and their subspecialty divisions. Primary and secondary outcome measures: Two reviewers extracted and coded research-related activities as learning outcomes, activities or assessments, by research stage (using, participating in or leading research) and competency based on Bloom's taxonomy (remembering, understanding, applying, analysing, evaluating, creating). We coded learning and assessment activities by type (eg, formal research training, publication) and whether it was linked to a scholarly project. Requirements related to project supervisors' research experience were noted. Results: Fifty-five of 58 Australian college subspecialty divisions had a scholarly project requirement. Only 11 required formal research training; two required an experienced research supervisor. Colleges emphasised a role for trainees in leading research in their learning outcomes and assessments, but not learning activities. Less emphasis was placed on using research, and almost no emphasis on participation. Most learning activities and assessments mapped to the 'creating' domain of Bloom's taxonomy, whereas most learning outcomes mapped to the 'evaluating' domain. Overall, most research learning and assessment activities were related to leading a scholarly project. Conclusions: Australian specialist college research curricula appear to emphasise a role for trainees in leading research and producing research deliverables, but do not mandate formal research training and supervision by experienced researchers.